1997
DOI: 10.1086/303987
|View full text |Cite
|
Sign up to set email alerts
|

The Protogalactic Origin for Cosmic Magnetic Fields

Abstract: It is demonstrated that strong magnetic fields are produced from a zero initial magnetic field during the pregalactic era, when galaxies are first forming. Their development proceeds in three phases. In the first phase, weak magnetic fields are created by the Biermann battery mechanism, acting in shocked parts of the intergalactic medium where caustics form and intersect. In the second phase, these weak magnetic fields are amplified to strong magnetic fields by the Kolmogoroff turbulence endemic to gravitation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
504
3
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(523 citation statements)
references
References 9 publications
14
504
3
2
Order By: Relevance
“…The non-linear turbulence effect plays an important role in generating and subsequently amplifying the created PMF which overcomes the damping mechanism due to the high plasma conductivity. The numerical simulations showed that the rms value for ∇·v ∼ ∇×v is about 10 −16 s −1 on comoving scale of Mpc at z ∼ 3 [20]. This is just the inverse of the time scale τ LSS for LSS formation.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The non-linear turbulence effect plays an important role in generating and subsequently amplifying the created PMF which overcomes the damping mechanism due to the high plasma conductivity. The numerical simulations showed that the rms value for ∇·v ∼ ∇×v is about 10 −16 s −1 on comoving scale of Mpc at z ∼ 3 [20]. This is just the inverse of the time scale τ LSS for LSS formation.…”
mentioning
confidence: 87%
“…It could be understood from the recent study in Ref. [20] where the battery mechanism has been proposed as a source for generating a small initial magnetic field during LSS formation. From the theory of small fluctuations, v will grow with density perturbations.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, converting the primordial seeds into those that may have existed at the protogalaxy formation epoch is by no means a trivial exercise (see, e.g. [53]). The question of whether or not the primordial seeds generated in PBB cosmology can evolve into the observed galactic magnetic fields thus remains, to this date, an unsolved, yet very interesting, problem.…”
Section: Gauge-field Perturbations: Seeds For B Gal ?mentioning
confidence: 99%
“…Braithwaite & Spruit 2004;Kulsrud et al 1997;Lovelace et a. 2009;Subramanian 2010;Widrow et al 2012).…”
Section: Introductionunclassified